VERTICO and illustrisTNG: the spatially resolved effects of environment on galactic gas - Stevens, Adam R. H.; Brown, Toby; Diemer, Benedikt; Pillepich, Annalisa; Hernquist, Lars; Nelson, Dylan; Bahé, Yannick M.; Boselli, Alessandro; Davis, Timothy A.; Elahi, Pascal J.; Ellison, Sara L.; Jiménez-Donaire, María J.; et al. (The astrophysical journal. Part 2, Letters, 2023)
It has been shown in previous publications that the TNG100 simulation quantitatively reproduces the observed reduction in each of the total atomic and total molecular hydrogen gas for galaxies within massive halos, i.e., dense environments. In this Letter, we study how well TNG50 reproduces the resolved effects of a Virgo-like cluster environment on the gas surface densities of satellite galaxies with m * > 109 M ⊙ and star formation rate > 0.05 M ⊙ yr−1. We select galaxies in the simulation that are analogous to those in the HERACLES and VERTICO surveys and mock-observe them to the common specifications of the data. Although TNG50 does not quantitatively match the observed gas surface densities in the centers of galaxies, the simulation does qualitatively reproduce the trends of gas truncation and central density suppression seen in VERTICO in both H i and H2. This result promises that modern cosmological hydrodynamic simulations can be used to reliably model the post-infall histories of cluster satellite galaxies.
Gesehen am 24.05.2024